Educational interventions to improve ergonomics in gastrointestinal endoscopy: a systematic review - Michael A. Scaffidi; Nikko Gimpaya; Andras B. Fecso; Rishad Khan; Juana Li; Rishi Bansal; Nazi Torabi; Amandeep K. Shergill; Samir C. Grover (Endoscopy International Open, 2022)
Background and study aims Endoscopists are at high risk of musculoskeletal pain and injuries (MSPI). Recently, ergonomics has emerged as an area of interest to reduce and prevent the incidence of MSPI in endoscopy. The aim of this systematic review was to determine educational interventions using ergonomic strategies that target reduction of endoscopist MSPI from gastrointestinal endoscopy. Methods In December 2020, we conducted a systematic search in MEDLINE, EMBASE, PsycINFO, Web of Science, Scopus, the Cochrane Central Register of Controlled Trials and the Cochrane Database of Systematic Reviews for articles published from inception to December 16, 2020. Studies were included if they investigated educational interventions aimed at changing knowledge and/or behaviors related to ergonomics in gastrointestinal endoscopy. After screening and full-text review, we extracted data on study design, participants, type of training, and assessment of primary outcomes. We evaluated study quality with the Medical Education Research Study Quality Instrument (MERSQI). Results Of the initial 575 records identified in the search, five met inclusion criteria for qualitative synthesis. We found that most studies (n = 4/5, 80 %) were single-arm interventional studies that were conducted in simulated and/or clinical settings. The most common types of interventions were didactic sessions and/or videos (n = 4/5, 80%). Two (40 %) studies used both standardized assessment studies and formal statistical analyses. The mean MERSQI score was 9.7. Conclusions There is emerging literature demonstrating the effectiveness of interventions to improve ergonomics in gastrointestinal endoscopy.